FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU NASABAH SIMPAN PINJAM PADA UNIT SIMPAN PINJAM (USP) SWAMITRA FATMA PESONA ADIKARYA PEKANBARU - Dewi, Diana Sri; Hastuti, Fitri (Sekolah Tinggi Ilmu Ekonomi Riau, 2018)
This reseach held at savings and loan unit Swamitra Fatma Pesona Adikarya Pekanbaru at Soekarno Hatta Street No.7E, The Morning Market Arengka Pekanbaru. This reaseach aims to knowing factors that influincing customer behaviour in borrowed funds at saving and loan unit Swamitra Fatma Pesona Adikarya Pekanbaru. Sample in this research as many as 60 respondents. Data were analyzed quantitatively by using validity test, reability, test F (simultaneous test), test T (partial test), multiple linear regression analysis, R-squer and classic assumption test. Result of this research shows that cultural factors and individual factors have a significant influence on customer decision in borrowed funds at saving and loan unit Swamitra Fatma Pesona Adikarya Pekanbaru, while social factors and psychological factors have no significant effect on customer decision saving and loan unit Swamitra Fatma Pesona Adikarya Pekanbaru. The result of this research analysis using help of SPSS 21.0. Based on the results obtained from the variabel Y (Customer Decision). Obtaired adjusted R-squer amount 0,740 or 74% while the remaining amount 26% influenced by anathor variabels which is ignored or not exsamined in this reseacrh